Copyright: Transfer of Book Copyright to Heirs by Civil Law - Ghuffran, Mohammad (Mahadi: Indonesia Journal of Law, 2025)
This paper aims to be able to find out an overview of the transfer of book copyright to heirs under civil law. IPR (intellectual property rights) is a right that arises because of the intellectual ability possessed by a human being in various fields, which can produce all kinds of things, starting from the process to producing a product or goods that have useful value. The result can be in the form of works in the fields of science, art, literature and also technology as a form of human intellectual creativity expressed through thoughts and ideas, the concept of intellectual property rights will be beneficial to all humans. The birth of book copyright began from an idea that arose from the idea of extorting the results of creativity and technology made by humans that utilize their intellectual intelligence and emotional abilities. Copyright can undergo a partial or total transfer of rights in the event of inheritance, will, waqf, grant, written agreement, or for other reasons as stipulated in the provisions of laws and regulations. The provisions of the regulation in terms of inheritance in the Civil Code consist of 2 ways, namely: the inheritance system "ab intestato" and the inheritance system according to the will "testament". The legal basis used in the implementation of inheritance in book copyright based on inheritance is inheritance law based on the Civil Code which regulates the position of a person's property after he or she dies by transferring the property to the rightful owner. Therefore, the transfer of book copyright that occurs as a result of this inheritance is able to transfer the whole related to exclusive rights where these exclusive rights consist of moral rights and economic rights of the creator. Keywords: Book Copyright, Transition, Heirs